The use of African American Vernacular English (AAVE) in three selected songs of Jay Park’s album The Road Less Traveled - Sheila Fathurrohmah; Ernie Diyahkusumaning Ayu Imperiani (Passage: Journal of English Language and Literature, 2024)
This study aimed to investigate and identify the linguistic feature of African-American Vernacular English (AAVE) used in the three selected songs of Jay Park’s album, The Road Less Traveled, and understand the underlying reasons for this AAVE use by applying sociolinguistic approach. The data were analyzed using several theories from Wolfram (2004), Fromkin et al. (2011), and Davenport and Hanna (2005) to analyse AAVE features and Cutler’s (2015) theory to analyze the underlying reasons why Jay Park employed AAVE in his songs. The data was gathered by attentively and comprehensively listening to the songs and reading the transcribed lyrics. The results were as follows: Jay Park used five out of the 13 grammatical features of African American Vernacular English, including copula absence, invariant be, remote been, specialized auxiliaries, and the use of "ain't" for negation. Additionally, he only employed two out of the proposed lexical features of AAVE, which are blends and clipping. Also, two phonetics features found in his music were regressive assimilation and deletion. Overall, the findings suggest that the use of AAVE by Jay Park in his songs is due to the authenticity of Hip-Hop culture regardless of the singer’s nationality and to express empathy and solidarity with the African-American community.